Reports on hospitals and the patient and a domestic workers' charter - Great Britain. Standing Joint Committee of Industrial Women's Organisations ; Labour Party (Great Britain). Advisory Committee on Public Health (London : Labour Party, 1931)
1931 1931 1930s 22 pages every two beds is a good working number. In all hospitals water beds are available as the need arises. As a rule, they are not alocated to particular wards. Locker. The details of the locker are matters of great importance to the patient, because a good locker will do much to take away the feeling of helplessness which a patient feels. Most of the lockers in English hospitals seem to be designed for inconvenience. The first necessity is that the locker should be higher than the bed, and washable, with a shelf on the level of the bed. It must have a ledge round three sides of it to prevent the fumbling movements of a patient pushing things off, and there should be provision for an adjustable soap dish and a towel rail at the back, and a tumbler. In some patterns there are adjustable bed tables fixed to an arm attached to the locker. These are better than no tables, but they are hardly firm enough for such processes as cutting up a meal. A wooden pocket on the side of the locker is a boon for newspapers and books, but it must be accessible to the patients. Bed Tables. The patient's ideal bed table consists of a china-topped table with firm legs on the floor, at each side of the bed, and coming four inches above its level. When not in use this stands across the foot of the bed, and on it the patient may keep her own flowers, and perhaps a photo. This table is a favourite with nurses, especially when the patient has to have her own crockery. Failing such large tables, the small ones with four 4 in. legs are quite good. Crockery. Whilst it is admitted that it is necessary to have thick china in a hospital, because of the rush of hospital life, yet there is no reason why it must be plain white. Even a coloured rim is better, but some kind of pattern makes just the difference to those who usually lack appetite. All feeding cups should be of such a pattern as can easily be cleaned. Spouts are taboo. Screens. Screens must be light in weight, fitted with rubber castors and well covered with a pretty patterned (8) 126/TG/RES/X/1036A/7